pull down to refresh

This inequality holds for any triangle:
\frac{1}{3} \leq \frac{a^2 + b^2 + c^2}{(a + b + c)^2} < \frac{1}{2}
where a, b and c correspond to the lengths of the triangle.
Can you prove it?
Previous iteration: #760106 (brief and corrected answer in #760229; I will write out a more detailed version of this same answer as well as an alternative approach using the tau function or divisor function, when I am a bit less tired)
First, we replace a=y+z, b=x+z, c=x+y with x, y, z > 0 being tangents on the inscribed circle, as in
The inequality thus becomes
\frac{1}{3} \leq \frac{(y+z)^2 + (x+z)^2 + (x+y)^2}{(y+z+x+z+x+y)^2} < \frac{1}{2}
which is
\frac{1}{3} \leq \frac{(x^2+y^2+z^2)+(xy+xz+yz)}{2(x^2+y^2+z^2)+4(xy+xz+yz)} < \frac{1}{2}
or
\frac{1}{3} \leq \frac{u+v}{2u+4v} < \frac{1}{2}
First, for the upper bound
\frac{u+v}{2u+4v} < \frac{1}{2}
2u+2v < 2u+4v
v > 0
which is obviously true because v is
xy + yz+ xz > 0
Second, for the lower bound
\frac{u+v}{2u+4v} \geq \frac{1}{3}
3u+3v \geq 2u+4v
u \geq v
Is equivalent to
x^2+y^2+z^2 \geq xy+yz+xz
x^2+y^2+z^2-xy-xz-yz \geq 0
(x-y)^2 + (x-z)^2 + (y-z)^2 >= 0
The sum must be >= 0 because each summand is.
reply
The inequality with 1/3 is a special case of the Cauchy inequality 😉
reply
Here's proof
"Answer to the Ultimate Question of Life, the Universe, and Everything"
reply